Optimizing respiratory system learning: The role of simple practicum teaching aids in improving cognitive and science process skills - Sholihah, Ika Zahrotus; Jalil, Muhamad; Setiawan, Aan (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2023)
Learning that leads to the achievement of cognitive aspects and science process skills needs to be improved. This research aims to determine the effectiveness of practice-based Biology learning on cognitive learning outcomes, science process skills, and student responses to respiratory system material. The research was conducted at one of the high schools in Demak Regency. The approach used in this research is a quantitative approach using experimental methods. The research design used was a non-equivalent control group. Sampling was carried out using purposive sampling. The sample in this research was all 58 class XI Science students. Data was collected by providing test questions and observation sheets and distributing questionnaires. The research results show that applying simple respiratory system training aids greatly improves cognitive learning outcomes. Students construct knowledge through experience. Applying simple, practical teaching aids for the respiratory system effectively develops students' science process skills. Students care about carrying out the science process by referring to worksheets adapted to the syntax of learning practices. Students' responses to applying practical teaching aids to the simple respiratory system were very good. Using simple props in demonstrations can help students understand difficult and abstract material.